IMPLEMENTASI PENANGGALAN DAYAK WEHEA DALAM KEGIATAN ADAT DI KAMPUNG DAYAK MUARA WAHAU - Nur Robaniyah; Nur Azizah , Maulidatun (ELFALAKY: Jurnal Ilmu Falak, 2023)
The Wehea Dayak is one of the Dayak tribes that still exist today. The Wehea Dayak tribe lives in close proximity to nature. They depend on the surrounding rivers, mountains, and forests. Daily activities cannot be separated from farming and hunting. This activity has a close relationship with the Dayak Wehea traditional activities. In determining the time of traditional activities, the Wehea Dayak people still use the Wehea Dayak calendar, which is a legacy from their previous ancestors. The Dayak Wehea calendar is unique among most calendars in Indonesia. The Wehea Dayak calendar only has two elements, namely the 29/30 months and the 10 periods. The Wehea Dayak calendar does not recognize years like other calendars. This research examines how the Dayak Wehea calendar is implemented in the traditional activities and rituals of the Dayak Wehea community in Muara Wahau District. This research is field research conducted in Muara Wahau District in August and December 2017. This research uses a qualitative approach to describe the research results. The results of this research explain that the Wehea Dayak people use this calendar for ten periods, which refers to traditional activities. This implementation includes determining the cutting period (Nep bloh), farming time (Nemeq), time to plant rice (Nugal), rituals in the fields (Entaglel), the ritual of welcoming the rice that begins to contain (Embeq Hemin Plai), harvest time (Neljiang), the period of completion of harvest (Mel Haq Pangseh May), rice feast (Erau/Lom Plai), time to make a hut (Naq Jengea), and finally the children's era/wedding party (Nak Lom).